‘Candidatus Mycoplasma haematonasua’ and tick-borne pathogens in ring-tailed coatis (Nasua nasua Linnaeus, 1976) from the Iguaçu National Park, Paraná State, southern Brazil - Collere, Flávia C. M.; Delai, Robson M.; Ferrari, Larissa D. R.; da Silva, Leticia H.; Fogaça, Pedro L. C.; Rodrigues, Apolonio N.; Gonçalves, Daniela Dib; Baggio, Rafael A.; Moraes, Marcela F. D. [UNESP]; Lux Hoppe, Estevam G. [UNESP]; André, Marcos R. [UNESP]; Vieira, Thállitha S. W. J.; et al. (Hindawi, 2021)
The Iguaçu National Park (INP) is the largest remnant of Atlantic Forest in southern Brazil, representing an ecological continuum with Argentina. The INP harbours a diverse fauna, with ring-tailed coatis (Nasua nasua Linnaeus, 1976, Carnivora: Procyonidae) in close contact with tourists either begging and/or snatching food from visitors. A potentially novel haemotropic Mycoplasma sp. has been previously detected in the ring-tailed coatis from central-western and southern Brazil. Therefore, the aims of this study were to investigate the occurrence of haemotropic Mycoplasma sp. and tick-borne pathogens in wild ring-tailed coatis from the INP, Foz do Iguaçu municipality, Paraná State, southern Brazil. Blood samples were collected from 18 wild ring-tailed coatis and evaluated by conventional PCR (cPCR) assays for haemotropic Mycoplasma spp. (16S and 23S rRNA), Theileria/Babesia spp. (18S rRNA) and Ehrlichia/Anaplasma spp. (16S rRNA, sodB, dsb and groEL). Eight out of 18 (44.44%; 95% CI: 24.56%–66.28%) animals were positive for haemotropic Mycoplasma spp. All ring-tailed coatis tested negative for Theileria/Babesia spp. and only one out of 18 (5.56%; 95% CI: 0.99%–25.76%) animals tested positive for Ehrlichia/Anaplasma spp. by the 16S rRNA cPCR. Unfortunately, multiple attempts to sequence the 16S rRNA gene of the Ehrlichia/Anaplasma-positive sample have failed. Phylogenetic and network analysis of the hemoplasma 16S and 23S rRNA gene fragments confirmed that animals were infected by a potentially novel haemotropic Mycoplasma sp. previously reported in ring-tailed coatis from Brazil. The name ‘Candidatus Mycoplasma haematonasua’ is proposed for this novel organism.
Keywords: Anaplasmataceae; haemoplasmas; haemotropic mycoplasmas; wild mammals